Exploring Partnership Work as a Form of Transformative Education: "You do your yapping and I just add in my stuff" - Greenstein, Anat; Blyth, Craig; Blunt, Christopher; Eardley, Clarence; Frost, Louise; Hughes, Richard; Perry, Barbara; Townson, Louise (Disability Studies Quarterly, 2015)
This paper details the work of a group of learning disabled people (people with intellectual disabilities) who contribute to the teaching of students undertaking a degree program at one of the UK's most elite universities. Traditional notions relating to knowledge production within academia are examined and we demonstrate how the participation of learning disabled people in classroom teaching challenges these. Drawing on the work of Freire (1972) the paper demonstrates how co-teaching by learning disabled people has a transformative impact on educational experiences. Finally, the current changes impacting the UK higher education sector are detailed and we explore how these changes are negatively impacting on courses that seek to move away from traditional approaches to pedagogy.